A Series of Experiments on Criticality and Reflector Reactivity Worth in FCA-XXIII-1 and FCA-XXIV-1 Assemblies Simulating a Small Fast Reactor with a Thick Stainless Steel Reflector - Masahiro Fukushima (2249263) (2025)
A series of integral experiments were conducted at the Fast Critical Assembly (FCA) of Japan Atomic Energy Agency using the FCA-XXIII-1 and FCA-XXIV-1 assemblies to simulate a small fast reactor (SFR) with a thick stainless steel reflector. The objective was to provide systematic data for assessing the effects of reflector configurations on the accuracy of neutronic calculations. FCA-XXIII-1 included multiple configurations with partial voids introduced into the reflector to enhance neutron leakage, while FCA-XXIV-1 utilized a depleted uranium blanket to ensure neutron shielding. This paper presents a detailed description of measurements of criticality and reflector reactivity worth under various reflector conditions. Calculations were performed using the MVP3 Monte Carlo code with the JENDL-5 nuclear data library. The calculated effective multiplication factors agreed with the experimental values within 300 pcm, with slight overestimations. Reflector reactivity worths were also well reproduced across configurations, regardless of neutron leakage levels. These results serve as benchmarks for validating computational codes and nuclear data libraries, and they thereby support the reliable design and analysis of SFRs with reflectors.